An Approach to Evaluating the Completeness of a Medical Knowledge Base - Bouhaddou, Omar (1989)
What is the list of Internal Medicine diseases? Which diseases in the list should be known by a student, a resident, an internist or a specialist? This papers reports on our approach to gathering the “complete” list of diseases in internal medicine and to categorizing in four groups the diseases to reflect the level of knowledge required of a student, a resident, an internist or a domain expert. This effort has provided us with a measure of how much an expert consultant program does “know” and what is the necessary coverage before the system is useful for each one of the four groups considered.